Self-assembly and semiconductivity of an oligothiophene supergelator - Pratihar, Pampa; Ghosh, Suhrit; Stepanenko, Vladimir; Patwardhan, Sameer; Grozema, Ferdinand C.; Siebbeles, Laurens D. A.; Würthner, Frank (Beilstein Journal of Organic Chemistry, 2010)
A bis(trialkoxybenzamide)-functionalized quaterthiophene derivative was synthesized and its self-assembly properties in solution were studied. In non-polar solvents such as cyclohexane, this quaterthiophene π-system formed fibril aggregates with an H-type molecular arrangement due to synergistic effect of hydrogen bonding and π-stacking. The self-assembled fibres were found to gelate numerous organic solvents of diverse polarity. The charge transport ability of such elongated fibres of quaterthiophene π-system was explored by the pulse radiolysis time resolved microwave conductivity (PR-TRMC) technique and moderate mobility values were obtained. Furthermore, initial AFM and UV-vis spectroscopic studies of a mixture of our electron-rich quaterthiophene derivative with the electron acceptor [6,6]-phenyl-C61-butyric acid methyl ester (PCBM) revealed a nanoscale segregated assembly of the individual building blocks in the blend.
Keywords: charge transport; hydrogen bonding; oligothiophene; organogel; self-assembly